Exploring actors' collaborations and involvement in the Namibian learner pregnancy policy - Shiningayamwe, Dorthea Nanghali Etuwete; Takeuchi, Shinichi (Frontiers in Education, 2024)
Investigating the Absence of Actor's Collaboration and Involvement in the Namibian Learner Pregnancy Policy: A case of selected Namibian Rural Schools Abstract Introduction: The Namibia Education Sector Policy on the Prevention and Management of Learner Pregnancy (ESPPMLP) aims to reduce the cases of learners falling pregnant and increase learner-parent completion of education. The ESPPMLP addresses the fact that learner pregnancy and school drop-out are collaborative efforts between parents, the community, schools, and non-governmental organizations. However, Namibia continues to have had a problem with the high rate of learner pregnancy and school drop-out for many years. Previous studies reported the absences and limitations of both internal and external actors' collaboration in its implementation. This paper aims to clarify the lack of stakeholder involvement and cooperation in the ESPPMLP activities within selected rural schools in Namibia. Methods: Using the qualitative approach mixed with phenomenological and content data analysis, the study conducted 19 individual interviews with schoolteachers, one school board member, one NGO representative, and six focus group discussions with 27 parents. Results and Findings: Among others, results show the limited life skills of teachers in schools, the attitude of the community towards schoolteachers, making them feel devoid of influence in collaborations, and the lack of sexual reproductive activities programs in school settings. The findings reveal the reliance of the activities of prevention and management of learner pregnancy on donor-driven initiatives, the lack of task forces at the community level, the shortage of knowledge and understanding about the ESPPMLP and the lack of policy implementation guidelines. Establish learner pregnancy leadership structures at the community level for coordination, coordinate learner pregnancy and school drop-out activities, introduce community parenting, and execute partnership of monitoring activities to boost stakeholder collaborations. Key Words: Stakeholders, Collaboration, Prevention, Management Learner-Pregnancy, Actors.